Evaluation of the Lower Trapezius Muscle Using Ultrasound Panoramic View (a Novel Approach): An Intra- and Inter-Rater Reliability Study - Fernández-Carnero, Samuel (Int J Environ Res Public Health, 2020)
The panoramic view ultrasound remains uncommon in clinical practice, probably because of its difficulty, high-cost, and lack of research. Morphological changes in muscles have been demonstrated to be related to symptomatology and provide data of interest for clinical assessment. Thus, the aim of this study was to evaluate the measurement reliability of the length of the lower trapezius muscle with the panoramic view ultrasound using a novel tool, SIG_VIP(®). Twenty healthy volunteers were measured by two expert sonographers using the SIG_VIP(®) tool with a novel approach. Statistical analyses were performed with the R software. The intraclass correlation coefficient (ICC), standard error of measurement (SEM), minimal detectable change (MDC), and Bland-Altman plots were calculated. All the results indicated good intra-rater reliability (ICC(3,1), 0.92 to 0.96; SEM, 0.59 to 0.85; MDC, 1.64 to 2.35) and inter-rater reliability (ICC(3,2), 0.84 to 0.89; SEM, 1.22 to 1.53; MDC, 3.39 to 4.25). The novel system used with the described methodology can reliably measure the length of the inferior fibers of the trapezius muscle. Further research must be conducted to evaluate the reliability in patients and how pathology is related to the length of the lower trapezius muscle.